SENSORY EVALUATION OF GOAT MILK CHEESE UNDER DIFFERENT FREEZING CONDITIONS - Eugenia Mihaela PRICOP (Stefan cel Mare University of Suceava, 2017)
The purpose of this paper is to investigate the effects of different freezing treatments on textural and sensorial characteristics of goat cheese in order to explore the possibility of storing for a longer period of time. Goat cheese samples were prepared from raw goat milk and treated under four different freezing methods:1) natural convection of air (- 200C); 2) deep freezing (-700C);3) immersion in eutectic solution of NaCl 23% and 4) cryogenic freezing using liquid nitrogen and compared with a control sample kept at 4-60C. After freezing, the samples were stored for 3 month at -18…-200C then they were thawed and stored for 14 days at 4…60C. The textural and sensory aspects were undertaken using 12 panelists. At the end, the samples were classified, depending on the score obtained from good to unsatisfactory.